2019
DOI: 10.1002/fsn3.945
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial content and associated risk factors influencing the quality of bulk tank milk collected from dairy cattle farms in Mandalay Region

Abstract: To investigate the bacterial content and risk factors associated with the hygienic quality of raw milk, a cross‐sectional study was conducted in four townships of Mandalay Region, Myanmar. From April to October 2017, bulk tank milk samples ( n = 233) were collected from 233 dairy cattle farms located in Tada‐U, Pyin Oo Lwin, Meiktila, and Patheingyi Townships. From each farm, approximately 100 ml of bulk tank milk was collected and examined for bacterial content. Total bacterial count (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
(45 reference statements)
4
8
2
Order By: Relevance
“…However, the majority of farmers in Asella area were not trained on hygienic milk production practices, which might play a role in increasing the bacterial load of bulk milk. Previous studies conducted in other parts of Ethiopia [53][54][55], Myanmar [56], Sri Lanka [57], India [58], Nigeria [59] and Burkina Faso [60] reported mean TBC counts higher than our finding. In contrast, lower mean TBC counts were reported in Gondar, Ethiopia [61], Tanzania [62], the USA [13,17,63,64], Belgium [8], Italy [10] and Ireland [49].…”
Section: Discussioncontrasting
confidence: 95%
“…However, the majority of farmers in Asella area were not trained on hygienic milk production practices, which might play a role in increasing the bacterial load of bulk milk. Previous studies conducted in other parts of Ethiopia [53][54][55], Myanmar [56], Sri Lanka [57], India [58], Nigeria [59] and Burkina Faso [60] reported mean TBC counts higher than our finding. In contrast, lower mean TBC counts were reported in Gondar, Ethiopia [61], Tanzania [62], the USA [13,17,63,64], Belgium [8], Italy [10] and Ireland [49].…”
Section: Discussioncontrasting
confidence: 95%
“…The surviving coliform population for plasma‐treated and untreated milk was determined using spread plate method in triplicates according to AOAC Official Methods of Analysis, sec (940.37B). The samples were serially diluted and particular aliquots were plated on violet red bile agar (Naing et al., 2019). The plates were then incubated for 24 hr at 37°C for colony enumeration and were expressed in log CFU/ml and % reduction.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of milk containing low bacterial counts lies in the fact that certain bacteria survive thermal processes, which could affect, in some way, the taste, texture or shelf life of milk [ 95 ], since bacteria can cause the spoilage of milk, as well as diseases that affect humans [ 96 ]. Therefore, when high microbial contents of milk are found, milk procurement needs to be improved [ 97 ]; for example, with proper disinfection, cleaning, storage and transportation of raw milk, it is guaranteed to be of good quality for consumption; likewise, by performing good milk handling practices, by training both the producers and actors involved in marketing and transportation, the quality of milk can be improved [ 98 ]. The pasteurization of milk seeks to eliminate pathogenic bacteria and guarantee the health of consumers, and it has been found that this heat treatment has a minimal effect on the nutritional characteristics of milk [ 99 ].…”
Section: Resultsmentioning
confidence: 99%